Anna Trosborg’s Request Speech Act Strategies in Spongebob Squarepants Selected Episodes - Abdussalam Jabaruddin Yamjirin; Agustin Eka Nuriati; Miftah Nugroho (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This research discusses the strategies of speech act of requests used in selected episodes of the animated series SpongeBob SquarePants based on Anna Trosborg’s concept in pragmatic studies. The aim of this research is to identify and analyze eight strategies grouped into 4 categories of speech act of requests used in the conversations of characters in the series. The episodes “Culture Shock,” “Help Wanted,” and “Band Geeks” from the SpongeBob SquarePants series were selected for their diverse situations, rich dialogues, and specifically because they depict a wide range of social interactions and character dynamics, which are critical for examining the nuances of request speech acts. The research gap in this study lies in the fact that previous studies have not explored the characters’ roles within the story and their positions involved in the dialogues under scrutiny, which is a crucial aspect of understanding the nuances of speech acts in different contexts. The research method used is qualitative descriptive with Miles and Huberman data analysis techniques to examine the speech act strategies of requests. Data were collected through film observation and translated into oral and written language. The research results indicate that in selected episodes of the animated series SpongeBob SquarePants, there are four categories of speech act of request strategies that can be found according to Anna Trosborg’s concept. This research contributes to understanding the application of speech act strategies in the context of animated films, as well as its relevance to pragmatic theory. Future research could build upon this study by examining the role of speech acts in various media platforms, focusing on those that cater to diverse age groups or cultural contexts. Researchers could also delve into how the use of speech acts in animated media shapes children’s and young adults’ perceptions and interactions with the world. Moreover, a comparative analysis of speech acts in animated films versus live-action films could offer valuable insights into the distinct communication strategies employed across different media formats.